Source of Crime in Islamic Psychological Perspective - Wahyu Kurniawan; Siti Hapsoh (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Crime is a problem that has long occurred, even since the beginning of the fall of the prophet Adam and Eve. So far, the problem of crime is only involved in information that comes from binding laws and regulations. Crimes that have been considered crimes are only limited to individuals who are trapped in the context of mistakes without explaining the origin of the source of the crime committed. About crime also tends to be discussed in the science of criminology. In the field of criminology, W Boger himself is divided into two, namely pure criminology that breeds criminal science in criminal anthropology, criminal sociology, criminal psychology, criminal psychopathology and neuropathology and phenology while applied criminology is criminal hygiene, criminal politics and criminalism. This writing is sharpened at the source of crime in the perspective of Islamic psychology. In Islamic psychology itself, crime is basically not much different from the psychological outlook developed by Freud's psychoanalysts such as explaining between Id, Ego and Super Ego, if in Islamic psychology the source of crime can be found in Nafs explanations such as Vegetable Nafs, Animal Nafs, and Human Insights . This crime has an explicit explanation in the Animal Nafs.